2018
DOI: 10.3389/fphar.2018.01204
|View full text |Cite
|
Sign up to set email alerts
|

Recent Update on the Pharmacological Effects and Mechanisms of Dihydromyricetin

Abstract: As the most abundant natural flavonoid in rattan tea, dihydromyricetin (DMY) has shown a wide range of pharmacological effects. In addition to the general characteristics of flavonoids, DMY has the effects of cardioprotection, anti-diabetes, hepatoprotection, neuroprotection, anti-tumor, and dermatoprotection. DMY was also applied for the treatment of bacterial infection, osteoporosis, asthma, kidney injury, nephrotoxicity and so on. These effects to some extent enrich the understanding about the role of DMY i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 67 publications
0
95
0
Order By: Relevance
“…Nrf2 is a key transcription factor that regulates antioxidant genes (such as CAT, SOD and HO-1) by combining with antioxidant response elements 33 . It has been shown that the activation of Nrf2 is related to cisplatin, acetaminophen and aristolochic acid in drug-induced nephrotoxicity 34 . Similarly, in HEK293 cells, after SDAP treatment, Nrf2 and its corresponding downstream HO-1, NQO1 protein levels increased significantly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a key transcription factor that regulates antioxidant genes (such as CAT, SOD and HO-1) by combining with antioxidant response elements 33 . It has been shown that the activation of Nrf2 is related to cisplatin, acetaminophen and aristolochic acid in drug-induced nephrotoxicity 34 . Similarly, in HEK293 cells, after SDAP treatment, Nrf2 and its corresponding downstream HO-1, NQO1 protein levels increased significantly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[6,13]. is compound was found to possess anticholinesterase [6], antiatherosclerosis (anti-inflammatory), antidiabetes, and antitumor activities and effects on cardioprotection, hepatoprotection, neuroprotection, and dermatoprotection [14].…”
Section: Determination and Elucidation Of Isolated Compoundsmentioning
confidence: 99%
“…Dihydromyricetin (DMY), which is the main flavonoid of AG with a content of up to 35% [7], showed antiproliferation capacities in lung [8], breast, [9], and ovarian cancer [10], improvements on hypertension [11], hyperlipidemia [12,13] and abnormal blood sugar levels [14], as well as neuroprotective activity against Alzheimer's disease [15], Parkinson's disease [16], alcohol addiction, depression [17], and dermatoprotection [18]. In addition, a preventive effect on myocardial fibrosis [19], myocardial hypertrophy [20], and cardiac ischemia/reperfusion injury [21] was reported.…”
Section: Introductionmentioning
confidence: 99%